Toward a better noninvasive assessment of preejection period: A novel automatic algorithm for B‐point detection and correction on thoracic impedance cardiogram. (7th March 2018) - Forouzanfar, Mohamad; Baker, Fiona C.; de Zambotti, Massimiliano; McCall, Corey; Giovangrandi, Laurent; Kovacs, Gregory T. A.
Abstract: Impedance cardiography is the most common clinically validated, noninvasive method for determining the timing of the opening of the aortic valve, an important event used for measuring preejection period, which reflects sympathetic beta‐adrenergic influences on the heart. Automatic detection of the exact time of the opening of the aortic valve (B point on the impedance cardiogram) has proven to be challenging as its appearance varies between and within individuals and may manifest as a reversal, inflection, or rapid slope change of the thoracic impedance derivative's (dZ/dt) rapid rise. Here, a novel automatic algorithm is proposed for the detection of the B point by finding the main rapid rise of the dZ/dt signal, which is due to blood ejection. Several conditions based on zero crossings, minima, and maxima of the dZ/dt signal and its derivatives are considered to reject any unwanted noise and artifacts and select the true B‐point location. The detected B‐point locations are then corrected by modeling the B‐point time data using forward and reverse autoregressive models. The proposed algorithm is validated against expert‐detected B points and is compared with different conventional methods; it significantly outperforms them by at least 54% in mean error, 30% in mean absolute error, and 27% in standard deviation of error. This algorithm can be adopted in ambulatory studies requiring beat‐to‐beat evaluation of cardiac hemodynamic parameters over extended time periods where expert scoring is not feasible.